(untitled) - Sha, Zhi Gang (New York, 2009)
This book gives you the soul secrets, wisdom, knowledge, and practices of this divine soul healing system. In this remarkable and uplifting guide to physical health, emotional wellness, and spiritual fulfillment, Dr. Sha reveals practical techniques to heal you, your loved ones, pets, relationships, finances, organizations, Mother Earth, and humanity.
Keywords: Spiritual life,Spiritual healing,Đời sống tinh thần,Chữa bệnh tinh thần